Structural morphing in a symmetry-mismatched viral vertex - Qianglin Fang (Nature Portfolio, 2020)
In icosahedral viruses, a symmetry-mismatched portal vertex is assembled by inserting a 12-fold-symmetric portal complex into a 5-fold-symmetric capsid environment. Here, the authors report a near-atomic-resolution in situ cryo-electron microscopy structure of this symmetrically mismatched viral vertex from bacteriophage T4.